Load-embedded inertial measurement unit reveals lifting performance. (July 2018) - Tammana, Aditya; McKay, Cody; Cain, Stephen M.; Davidson, Steven P.; Vitali, Rachel V.; Ojeda, Lauro; Stirling, Leia; Perkins, Noel C.
Abstract: Manual lifting of loads arises in many occupations as well as in activities of daily living. Prior studies explore lifting biomechanics and conditions implicated in lifting-induced injuries through laboratory-based experimental methods. This study introduces a new measurement method using load-embedded inertial measurement units (IMUs) to evaluate lifting tasks in varied environments outside of the laboratory. An example vertical load lifting task is considered that is included in an outdoor obstacle course. The IMU data, in the form of the load acceleration and angular velocity, is used to estimate load vertical velocity and three lifting performance metrics: the lifting time (speed), power, and motion smoothness. Large qualitative differences in these parameters distinguish exemplar high and low performance trials. These differences are further supported by subsequent statistical analyses of twenty three trials (including a total of 115 total lift/lower cycles) from fourteen healthy participants. Results reveal that lifting time is strongly correlated with lifting power (as expected) but also correlated with motion smoothness. Thus, participants who lift rapidly do so with significantly greater power using motions that minimize motion jerk. Highlights: New experimental method using load-embedded IMU for manual lifting performance. Lifting performance measured by lifting time, power and motion smoothness. Rapid lifting associated with high power and minimum motion jerk.